Factors affecting adoption of improved farm practices by the farmers of Northern Bangladesh - Farid, KS; Tanny, NZ; Sarma, PK (Journal of the Bangladesh Agricultural University, 2016)
The present research examined the extent of adoption of improved farm practices by the farmers of Northern Bangladesh and determined the influencing factors for adopting these practices. This study was carried out in purposively selected Parbatipur upazila of Dinajpur district and Sherpur upazila of Bogra district as a representative of the northern Bangladesh. Data were collected from randomly selected 218 farmers through pre-tested interview schedule. Various descriptive and inferential statistical techniques were applied for getting meaningful results. Findings portray that most of the respondents belong to middle age group with a mean age of 47.02 years. The highest 37.2 percent of the respondents completed secondary level of education. Agriculture is the primary occupation of 89 percent of the respondents. The farmers have very low level of participation in various organizations. Contact with various communication media is very low for Sherpur compared to Parbatipur. The farm practices adopted mainly by the farmers are modern varieties, line sowing, power tiller, optimum tillage, balanced fertilizer, STW/DTW, IPM, balanced irrigation, rice weeder, sprayer and threasure. Among all practices, power tiller adoption is the highest and line showing is the lowest. Mean adoption score is 70.60. Results of multiple regression model indicates that communication score, total cultivable land, and socio-economic score have significant positive relationship, and total land area affected due to drought has significant negative relationship with adoption of improved farm practices by the farmers. Moreover, logistic regression model portrays that technology adoption is 1.49 times lower for Sherpur compared to Parbatipur. Finally, we can say that socio-economic factors influencing adoption of improved farm practices may be taken into consideration while accelerating the face of technology adoption under farming system. J. Bangladesh Agril. Univ. 13(2): 291-298, December 2015